Literature Analysis of Cash Waqf: Trends and Future Research Agenda (ZISWAF: Jurnal Zakat dan Wakaf, 2023)
This research aims to determine the trend of the cash waqf analysis published in Scopus-indexed journals. The data were obtained from Scopus on December 07, 2022, with a bibliometric and SLR analysis used through VOSViewer software and Ms. Excel as the analysis tool. The results showed that the 93 documents on the trend of cash waqf increased in recent years. Meanwhile, the distribution emphasized the type of 80 documents (86%), 6 Book Chapters (7%), 4 Reviews (4%), and 3 Conference Papers (3%) contained, with English (92%) being the language most widely used. The productive journal containing articles with the theme of cash waqf was also the Isra International Journal of Islamic Finance (8), with the most productive author, country, and institution being Gürsoy C. (5) and Malaysia (51), and International Islamic University (Malaysia), respectively. For the most cited, inspiring article, and author in cash waqf research, Mohammed M.O. (33) was observed. Based on the keyword, density, overlay, and recent article SLR investigations, at least 16, 10, 10, and 10 topics were determined, respectively. From these results, many opportunities were still capable of being conducted and highly studied regarding cash waqf.